Taurine ameliorates water avoidance stress-induced degenerations of gastrointestinal tract and liver - ERCAN, FERİHA; ŞENER, GÖKSEL; ÇETİNEL, ŞULE (SPRINGER, 2006)
We investigated the role of taurine, is a potent free radical scavenger, on water avoidance stress (WAS)induced degeneration of the gastric, ileal, and colonic mucosa and liver parenchyma. Wistar albino rats were exposed to chronic WAS (WAS group) 2 hr daily for 5 days. After exposing animals to chronic WAS (WAS + taurine group), 50 mg/kg taurine was injected IP for 3 days. Control animals received vehicle solution only. The stomach, ileum, colon, and liver samples were investigated under light microscope for histopathologic changes. To demonstrate the topography of the luminal mucosa of the stomach, ileum, and colon, scanning electron microscope was used and for hepatocyte ultastructure transmission electron microscope was used. Malondialdehyde (MDA, a biomarker of oxidative damage) and glutathione (GSH, a biomarker of protective oxidative injury) levels were also determined in all tissues. In the WAS group, the stomach epithelium showed ulceration in some areas, dilatations of the gastric glands, and degeneration of gastric glandular cells; prominent congestion of the capillaries was apparent. In the WAS group, severe vascular congestion was observed along with degeneration of ileal and colonic epithelium. Prominent vascular congestion and dilated sinusoids, activated Kupffer cells, dilated granular endoplasmic reticulum membranes, and focal pyknotic nuclei were observed in liver parenchyma. MDA levels (stomach, P < 0.01; ileum, colon, and liver P < 0.05) were increased and GSH levels (P < 0.01) were decreased in all tissues in the WAS group compared with the control group. The morphology of gastric, ileal, and colonic mucosa and liver parenchyma in the WAS + taurine group (stomach and ileum, P < 0.05; colon and liver, P < 0.01) showed a significant amelioration when compared to the WAS g roup. Increased MDA and decreased GSH levels in the WAS group were ameliorated with taurine treatment. Based on the results, taurine supplementation effectively attenuates the oxidative damage of gastrointestinal mucosa and liver because of WAS induction possibly by its antioxidant effects.
Keywords: water avoidance stress; stomach; ileum; colon; liver; morphology; lipid peroxidation; glutathione; taurine; MUCOSAL BLOOD-FLOW; EPITHELIAL BARRIER; OXIDATIVE STRESS; INDUCED TOXICITY; COLD-RESTRAINT; FREE-RADICALS; NITRIC-OXIDE; RAT; DAMAGE; INFLAMMATION